Recommendation for a Pilot MCDA Tool to Support the Value-Based Purchasing of Generic Medicines in the UAE - Farghaly, Mohamed Naser; Al Dallal, Sara Ahmad Mohammad; Fasseeh, Ahmad Nader; Monsef, Nahed AbdulKhaleq; Suliman, Eldaw Abdalla Mohamed Ali; Tahoun, Mohamed Attia; Abaza, Sherif; Kaló, Zoltán (Frontiers in Pharmacology, 2021)
Introduction: In recent periods the United Arab Emirates (UAE) has strengthened economic measures in its pharmaceutical policy by promoting local manufacturing and facilitating the use of generic medicines. International examples indicate the importance of quality control elements in the implementation of cost containment policies. Multicriteria Decision Analysis (MCDA) is increasingly used in health care to facilitate health care decision based on multiple objectives. Our objective was to develop a pilot MCDA tool for repeated use to support the value-based purchasing of generic medicines in the UAE. Methods: An international evidence framework was adapted to UAE in a multistakeholder workshop organized by Dubai Health Authority. After validating the relevance of nine criteria in the local jurisdiction, participants decided the ranking and weight of each criterion by anonymous voting. Results: The top four criteria focused on quality elements starting with real-world clinical or economic outcomes (with 19.8% weight), followed by the quality assurance of manufacturing (17.3%), then evidence on the equivalence with the original product (14.8%), and drug formulation and stability (12.3%). The pharmaceutical acquisition cost criteria ranked fifth with 9.4% weight. The bottom four criteria, including reliability of drug supply, macroeconomic benefit, pharmacovigilance and added value services related to the product had similar weights in the range of 5.5–7.7%. Conclusion: Policy-makers in Dubai put high emphasis of value-based health care by incentivizing manufacturers of off-patent pharmaceuticals to generate additional scientific evidence compared to the mandatory minimum and acknowledging efforts to improve quality standards. The MCDA tool is considered suitable to improve the transparency and consistency of decision making in UAE for off-patent pharmaceuticals, and subsequently for other health technologies.